An optimal dose‐fractionation for stereotactic body radiotherapy in peripherally, centrally and ultracentrally located early‐stage non‐small lung cancer - Izabela Zarębska; Maciej Harat (Thoracic Cancer, 2023)
Abstract Stereotactic body radiotherapy (SBRT), also known as stereotactic ablative radiotherapy (SABR), is commonly used in inoperable patients with early‐stage non‐small lung cancer (NSCLC). This treatment has good outcomes and low toxicity in peripherally located tumors. However, in lesions which are located close to structures such as the bronchial tree or mediastinum the risk of severe toxicity increases. This review summarizes the evidence of dose‐fractionation in SBRT of NSCLC patients in various locations.